Multiple Scattering Theory for Spectroscopies A Guide to Multiple Scattering Computer Codes -- Dedicated to C. R. Natoli on the Occasion of his 75th Birthday (Springer Proceedings in Physics,, 2018)
This edited book, based on material presented at the EU Spec Training School on Multiple Scattering Codes and the following MSNano Conference, is divided into two distinct parts. The first part, subtitled "basic knowledge", provides the basics of the multiple scattering description in spectroscopies, enabling readers to understand the physics behind the various multiple scattering codes available for modelling spectroscopies. The second part, "extended knowledge", presents "state- of-the-art" short chapters on specific subjects associated with improving of the actual description of spectroscopies within the multiple scattering formalism, such as inelastic processes, or precise examples of modelling.